2004
DOI: 10.1245/aso.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Size and Shape of Necrosis Induced by Radiofrequency Ablation in Human Livers: A Volumetric Evaluation

Abstract: The diameter of RFA-induced liver necrosis is significantly smaller than expected from needle deployment, especially with full-needle deployment. The shape of the lesion differs in more than half of the cases from the anticipated spherical pattern. The upper limit for reproducible necrosis induction is a tumor diameter of 3.4 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 14 publications
1
39
1
2
Order By: Relevance
“…Since most lumps or tumors are roughly spherical or ellipsoid in shape [40], detection of surface curvature is important for observing the presence of a lump and estimating its size. Goodwin et al stimulated the human finger pad with rigid spherical stimuli of varying radii, and showed that slight changes in curvature (especially for stimuli smaller than a single finger pad) can drastically effect the firing rate of SA I mechanoreceptors [12,14] and the perception [13] of the stimulus curvature.…”
Section: Softness Discriminationmentioning
confidence: 99%
“…Since most lumps or tumors are roughly spherical or ellipsoid in shape [40], detection of surface curvature is important for observing the presence of a lump and estimating its size. Goodwin et al stimulated the human finger pad with rigid spherical stimuli of varying radii, and showed that slight changes in curvature (especially for stimuli smaller than a single finger pad) can drastically effect the firing rate of SA I mechanoreceptors [12,14] and the perception [13] of the stimulus curvature.…”
Section: Softness Discriminationmentioning
confidence: 99%
“…Additionally, alternative treatments such as the use of tumor ablation with radiofrequency devices also have the potential to be quantified using tumor volumetric evaluation. 16 While liver lesions are commonly assessed with contrastenhanced CT, many patients also undergo combined PET/ CT. In PET/CT, the PET information is used to determine the functional status of the tissue, while the CT is used for PET attenuation correction and localization.…”
Section: ͒mentioning
confidence: 99%
“…With current electrodes, large ablation zones can be obtained but their predictability and completeness is problematic. Size and shape of the ablation zone are highly variable and difficult to predict [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] even in the most standardised ex vivo experiments (Table 1). A standard deviation of the ablation diameter, especially the transverse diameter, of 0.5-1 cm is very common (Table 1).…”
Section: Introductionmentioning
confidence: 99%